ZnS/ZnO nanosheets obtained by thermal treatment of ZnS/ethylenediamine as a Z-scheme photocatalyst for H2 generation and Cr(VI) reduction - Poliukhova, V.; Khan, S.; Qiaohong, Z.; Zhang, J.; Kim Doyeon; Kim, Seung chul; Cho, So Hye (Elsevier BV, 2022)
In this study, ZnS/ethylenediamine nanosheets were obtained by solvothermal synthesis and modified into composites of ZnS and ZnO by heat treatment. Compared to pure ZnO and ZnS, the ZnS/ZnO composite showed superior photocatalytic activity towards hydrogen evolution from water (500 ？mol h？1 g？1) and photoreduction of toxic Cr(VI) (k = 0.0078 min？1). Rietveld refined XRD patterns, high resolution-transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and UV？vis diffuse reflectance spectra (DRS) clearly showed that the composite forms a heterojunction structure instead of a solid solution of ZnS and ZnO. Density functional theory (DFT) modeling was conducted on a heterojunction interface and suggested that anion defects (S- and O-deficient) can allow Z-scheme photocatalysis to occur. The defect states in ZnS/ZnO composite were confirmed by XPS and electron paramagnetic resonance (EPR) measurement, suggesting the presence of oxygen vacancies. The defects create a deep energy state within bandgaps of ZnS and ZnO, which attracts holes from ZnS's valence band and electrons from ZnO's conduction band. Thereby electrons at the ZnS's conduction band and holes at ZnO's valence band are secured, allowing enhanced redox capability. ？ 2021